Association between Serum Calcidiol Levels and Cognitive Function in Geriatric Patients - Anandhita, Sandy; Budiningsih, Fatichati; Nurrudhin, Arief (Indonesian Journal of Medicine, 2020)
Background: The role of vitamin D toward cognitive function is as neuroprotective in which vitamin D will increase neurotrophic factor production which contributes to supporting neuron life sustainability, development, and function. The study aims to analyze the association between calcidiol serum level and cognitive functions of geriatric patients.Subjects and Method: A cross-sectional study was conducted at Geriatric Polyclinic of dr. Moewardi Hospital, Surakarta. A sample of 30 geriatric patients was selected randomly. The dependent variable was cognitive functions (MMSE score). The Independent variable was calcidiol serum level. The data were analyzed by Spearman test.Results: There was no difference of calcidiol serum level with MMSE score (OR= 1.00; p= 0.478).Conclusion: There was no difference in calcidiol serum level with MMSE score.Keywords: cognitive functions, calcidiolCorrespondence: Sandy Anandhita. Masters Program in Family Medicine, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta, Central Java. Email: anandhitasandy3@gmail.com. Mobile: 082227940410Indonesian Journal of Medicine (2020), 05(03): 185-190https://doi.org/10.26911/theijmed.2020.05.03.02